The NAC transcription factor family in Eucommia ulmoides: Genome-wide identification, characterization, and network analysis in relation to the rubber biosynthetic genes - Zhang, Shuwen; Xu, Tingting; Ren, Yongyu; Song, Lianjun; Liu, Zhao; Kang, Xiangyang; Li, Yun (Frontiers in Plant Science, 2023)
The NAC transcription factor family is a large plant gene family, participating in plant growth and development, secondary metabolite synthesis, biotic and abiotic stresses responses, and hormone signaling. Eucommia ulmoides is a widely planted economic tree species in China that can produce trans-polyisoprene: Eucommia rubber (Eu-rubber). However, genome-wide identification of the NAC gene family has not been reported in E. ulmoides. In this study, 71 NAC proteins were identified based on genomic datasets of E. ulmoides. These proteins were divided into 17 subfamilies based on their phylogenetic relationships. The gene length, molecular weights, isoelectric points, aliphatic index, and grand average of hydropathicity of the identified NAC family members varied, while the gene structure and motifs were relatively conserved. Chromosomal location analysis revealed that the EuNAC genes were unevenly distributed on 16 chromosomes; three pairs of genes of tandem duplicates and 12 segmental duplications were detected. Analysis of gene expression patterns in tissues and co-expression networks showed that the EuNAC genes were closely related to Eu-rubber biosynthesis and were responsive to hormone treatment. These results will provide a useful reference for further studies addressing the functional characteristics of the NAC gene and its potential role in Eu-rubber biosynthesis.